Policy lags and exchange rate dynamics in Nigeria: Any evidence? - Ayinde Taofeek Olusola (Department of Development Economics, Universitas Sriwijaya, 2020)
The study investigates policy lags and exchange rate dynamics in Nigeria. The downswing in the Nigerian economy attributed to recurring exchange rate fluctuations justifies this empirical investigation. The period of investigation spans 1970 – 2016 and the data were obtained from the various issues of the Central Bank of Nigeria (CBN) Statistical Bulletin and the Annual Statistics of the National Bureau of Statistics (NBS). Anchored on the monetary theory of exchange rate, the Markov-Switching Dynamic Regression (MSDR) was employed as the technique of analysis. The findings show that the supply of broad money in Nigeria is endogenous in nature as it serves as the adjustment variable for the stabilization of exchange rate in the economy. Also, the results obtained indicated that changes in the exchange rate affect the overall government income and that the Nigerian economy is still foreign dependent. An expansionary monetary policy takes three (3) years to stabilize exchange rate in Nigeria while an expansionary fiscal policy only takes one and a half (11/2) years. By implication, monetary policy is half-effective as the fiscal policy. Besides, there is evidence of fiscal dominance in Nigeria. The study found two exchange regimes of fixed- and managed-float. More so, fixed exchange rate regime in Nigeria was just not persistent but that the probability of transiting to a managed-float regime was relatively lower.